CYFRA 21‐1 and CEA combination assay in EMPD. (1st September 2019) - Nakamura, Y.; Tanese, K.; Hirai, I.; Amagai, M.; Kawakami, Y.; Funakoshi, T.
Summary: Extramammary Paget's disease (EMPD) is a rare skin cancer affecting the genitals and armpit regions. EMPDs occur mainly in Caucasian women and Asian men over the age of 60, in less than 0.6 per 100, 000 people. Basic treatment is excision (removal) by operation, yet metastasis, meaning that it has spread, is seen in around 10% of patients. If the cancer is spreading, it is really important to detect this and start treatment as early as possible, since in late stages the disease can be hard to treat. A biomarker, or marker, is a molecule found in blood, different levels of which correspond with how well the body responds to a treatment, or to how the disease will progress. Carcinoembryonic antigen (CEA) and cytokeratin 19 fragment 21‐1 (CYFRA 21‐1) are both biomarkers for certain other cancers, and it has been suggested that they might also be markers for monitoring tumour progression in EMPD; however, neither the accuracy of, nor correlation between, these markers have been examined in EMPD patients. This study from Japan aimed to find out the usefulness and relationship of CEA and CYFRA21‐1 levels in blood of EMPD patients in various progression states of the disease. A total of 30 EMPD cases were included in this study. In all early‐stage patients, CEA and CYFRA were within normal levels. In advanced‐stage patients, CEA and CYFRA were elevated in 79% and 63%, respectively. Either CEA or CYFRA was found to be elevated in 95% of the advanced patients, indicating that a certain number of patients have raised levels of only one of the markers. In addition, both of the markers also correlated well with the treatment responses in all patients. This study revealed that examining both CEA and CYFRA may help to detect advanced‐stage EMPD patients, and that they are useful for monitoring treatment responses.